Association study of polymorphism in Thrombomodulin gene [rs1042579] with cardiovascular disease - Khosravi, Elham; Sadeghian, Ladan; Mohamadynejad, Parisa; Dianatkhah, Minoo; Hajizadeh, Mahsa; Gharipour, Mojgan (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Thrombomodulin (THBD) gene plays an important role in activation and control of protein C. Regulation protein C levels as an important risk factor for cardiovascular disease. Mutations in this gene can affect Thrombomodulin levels. In this study, we aimed to investigate the role of single nucleotide polymorphism (SNP) in rs1042579 THBD gene in patients with cardiovascular disease. Methods: The samples of this case-control study consisted of 105 Iranian patients with cardiovascular disease and 95 healthy controls who enrolled from March 2017 to December 2018 in this study. Demographic data, medical history, and para-clinical were measured, and Sanger sequencing was used for allelic discrimination. Control samples were identified and then selected for genotyping of other ARMS-PCR technique. Results: Data analysis revealed that the rs1042579 polymorphism of the THBD gene was associated with a risk of coronary heart disease. Sequencing results confirmed the existence of CC homozygous, heterozygous TC and TT homozygous genotypes. TT genotype is a risk factor in patients compared to healthy controls. Conclusion: The results of this study showed that the rs1042579 polymorphism was associated with an increased risk of cardiovascular disease.